2020
DOI: 10.1007/s00702-020-02205-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic analyses of panic disorder in the post-GWAS era

Abstract: Panic disorder (PD) is a common and debilitating neuropsychiatric disorder characterized by panic attacks coupled with excessive anxiety. Both genetic factors and environmental factors play an important role in PD pathogenesis and response to treatment. However, PD is clinically heterogeneous and genetically complex, and the exact genetic or environmental causes of this disorder remain unclear. Various approaches for detecting disease-causing genes have recently been made available. In particular, genome-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…However, very small effects are not specific for research on personality traits. For example, individual genes can only account for a very small proportion of variance and individual differences in these effects based on epigenetic variants may be even harder to detect (Holland et al, 2016; Morimoto et al, 2020; Mott, 2022; Sullivan, 2010). Thus, learning from this area of research, we probably need large-scale, multi-lab, multi-national studies with many more participants than are customary in personality change research to better understand the implications of life events (Bleidorn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, very small effects are not specific for research on personality traits. For example, individual genes can only account for a very small proportion of variance and individual differences in these effects based on epigenetic variants may be even harder to detect (Holland et al, 2016; Morimoto et al, 2020; Mott, 2022; Sullivan, 2010). Thus, learning from this area of research, we probably need large-scale, multi-lab, multi-national studies with many more participants than are customary in personality change research to better understand the implications of life events (Bleidorn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, very small effects are not specific for research on personality traits. For example, individual genes can only account for a very small proportion of variance and individual differences in these effects based on epigenetic variants may be even harder to detect (Holland et al, 2016;Morimoto et al, 2020;Mott, 2022;Sullivan, 2010). Thus, learning from this area of research, we probably need largescale, multi-lab, multi-national studies with several many more participants than are customary in personality change research to better understand the implications of life events (Bleidorn et al, 2020).…”
Section: Implications For Future Research On Individual Differences I...mentioning
confidence: 99%
“…In addition, whole exome sequencing is increasingly used to investigate rare variants. However, to date no rare variant associations have been found for anxiety disorders (Gregersen et al, 2016; Kawamura et al, 2011; Morimoto et al, 2020) (See list of preliminary findings in Table 2). This is not surprising as GWAS in anxiety disorders have already shown that more than 100 000 individuals are needed for stable results on common variants and previous studies on rare variants have been far from this sample size.…”
Section: Molecular Geneticsmentioning
confidence: 99%